Revisiting the empirical model `Phases in the junior-to-senior transition of Swedish ice hockey players`: External validation through focus groups and interviews - Pehrson, S.; Stambulova, N. B.; Olsson, K. (International Journal of Sports Science & Coaching, 2017)
In this study, we continue to explore the junior-to-senior transition process in Swedish ice hockey by validating the empirical model `Phases in the junior-to-senior transition of Swedish ice hockey players` created in our previous study.1 More specifically, we collected opinions and critical reflections of 15 senior professional players and expert coaches about the empirical model as a whole and about the content of each junior-to-senior transition phase and then converted the original empirical model into its validated version. Professional ice hockey players and first league coaches formed three focus groups, while three senior coaches were interviewed individually. All were encouraged to critically reflect on the empirical model. The data from all sources were analysed following guidelines of the thematic (deductive) analysis complemented by quantitative measurements of the participants` agreement with the content of the empirical model. Results supported the sequence and designations of the junior-to-senior transition phases (i.e. preparation, orientation, adaptation and stabilization), as well as duration of the junior-to-senior transition (i.e. up to four seasons) outlined by the empirical model. We were also able to validate the psychological content (perceived demands, resources, barriers, coping strategies and outcomes) of each transitional phase. Accordingly, five themes were reformulated, 17 new themes were added and some themes were re-ordered during the conversion of the original empirical model into the validated model. To improve the readability of the validated model (from the bottom to the top), we also re-ordered sub-categories describing the psychological content of each junior-to-senior transition phase. We conclude by discussing the validated model in relation to theoretical frameworks and previous research and providing some methodology, future research and practice-oriented reflections addressed to researchers, coaches and sport psychology practitioners. ABSTRACT FROM AUTHOR